3 days to live [large type] - Patterson, James, 1947-; Swierczynski, Duane; Schweigart, Bill; Hogben, Julie Margaret (Grand Central Publishing Large Print, 2023)
Three stories of suspense, including "3 Days to Live," in which a CIA-agent bride is on her European honeymoon when she and her husband are poisoned--leaving her seventy-two hours to take revenge